Formwork Implementation Methods for Reinforced Concrete Column Structures Using PERI System - Reynold Andika Pratama; Marysca Shintya Dewi; Wildan Abdul Jabar; Aryo Bismoko (International Journal Multidisciplinary Science, 2025)
This study investigates the implementation methods of the PERI formwork system for reinforced concrete column structures in the KAI CO-Living Gondangdia project, an 8-story residential building in Central Jakarta. Employing a qualitative case study approach, the research documents the assembly, installation, concrete placement, and removal processes of the PERI system during a three-month internship. Key aspects analyzed include material preparation, panel assembly, alignment techniques, quality control measures, and safety protocols. The PERI system, characterized by modular steel-framed panels and phenolic-coated plywood, facilitated rapid assembly (45-60 minutes per column), high dimensional accuracy (±3mm tolerance), and excellent concrete surface quality for 85% of columns. The system’s reusability (24 cycles) and reduced labor requirements (25% less than traditional methods) enhanced project efficiency. Standardized procedures, skilled labor, and rigorous quality control were critical to success, though specialized training was necessary. The findings highlight the PERI system’s advantages in speed, quality, and cost-effectiveness for repetitive structural elements, offering practical insights for optimizing formwork in modern construction. Recommendations include investing in crew training, detailed planning, and comprehensive quality protocols to maximize system benefits.